100 Years of Radar - Galati, Gaspare (Springer International Publishing : Imprint: Springer, 2016)
This book offers fascinating insights into the key technical and scientific developments in the history of radar, from the first patent, taken out by Hülsmeyer in 1904, through to the present day. Landmark events are highlighted and fascinating insights provided into the exceptional people who made possible the progress in the field, including the scientists and technologists who worked independently and under strict secrecy in various countries across the world in the 1930s and the big businessmen who played an important role after World War II. The book encourages multiple levels of reading. The author is a leading radar researcher who is ideally placed to offer a technical/scientific perspective as well as a historical one. He has taken care to structure and write the book in such a way as to appeal to both non-specialists and experts. The book is not sponsored by any company or body, either formally or informally, and is therefore entirely unbiased. The text is enriched by approximately three hundred images, most of which are original and have been accessed by detailed searches in the archives.